2010
DOI: 10.1007/s00464-010-0899-z
|View full text |Cite
|
Sign up to set email alerts
|

Band erosion after laparoscopic gastric banding: a retrospective analysis of 865 patients over 5 years

Abstract: The overall incidence of LAGB erosions in our series was 1.96%. This incidence fell with increasing experience to 0.5% after the initial 300 bands were excluded from the analysis (3 band erosions in the last 565 band insertions). However, further increases in incidence are likely with a longer follow-up period. The most common presentation was abdominal pain followed by weight regain and port-site sepsis. In the authors' hands, laparoscopic omental plugging and band removal through a separate anterior gastroto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 23 publications
3
58
1
Order By: Relevance
“…A multiple regression analysis shows that erosion rate is signifi cantly predicted by number of patients and number of years of surgeon experience. As stated by Cherian et al [18], 55% of the erosions occur within the fi rst year, and only 10% after the second year of LAGB placement, the gastric band erosion can be as high as 17% in reports involving less than 100 patients. It has been generally accepted that early GBE is related to micro-injury during surgery, while late GBE is linked to foreign body responses caused by chronic ischemic tissue damage, however, the etiology of GBE is still not understood at all.…”
Section: Discussionmentioning
confidence: 92%
“…A multiple regression analysis shows that erosion rate is signifi cantly predicted by number of patients and number of years of surgeon experience. As stated by Cherian et al [18], 55% of the erosions occur within the fi rst year, and only 10% after the second year of LAGB placement, the gastric band erosion can be as high as 17% in reports involving less than 100 patients. It has been generally accepted that early GBE is related to micro-injury during surgery, while late GBE is linked to foreign body responses caused by chronic ischemic tissue damage, however, the etiology of GBE is still not understood at all.…”
Section: Discussionmentioning
confidence: 92%
“…Christou and Efthimiou [19] reported six erosions observed during the first 18 months after surgery. Cherian et al [6] reported presentation of erosion in 10/17 patients during the first year and only 2 after the second year from band positioning. These authors support the hypothesis that intragastric migration is multifactorial, suggesting a different etiology depending on the timing of complication: early erosion could be related to iatrogenic microinjuries at the time of band insertion, while a delayed appearance could be due to a combination of insults to the gastric serosa, including ischemia and foreign body reaction or high internal pressure as a result of ingestion of excessively large food boluses early after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Hypovolemic shock with massive upper gastrointestinal hemorrhage due to erosion into the celiac axis or in the left gastric artery has been reported, as well as small bowel obstruction due to intragastric band erosion [24][25][26]. In most cases, clinical symptoms are absent or mild and transient, and many authors agree that a pathognomonic manifestation of intragastric erosion is absent [1][2][3][4][5][6]14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations